Invasive wild boar in Argentina: using protected areas as a research platform to determine distribution, impacts and management - Ballari, Sebastián A. (2015)
The wild boar is an invasive ecosystem engineer in Argentina that has lacked sufficient basic information to determine applied actions. The current distribution, impacts and management of this species were analyzed using the expert opinion surveys of protected area managers. The boar is widely distributed and occupies most of Argentina?s terrestrial ecoregions. Moreover, its populations are common, and its abundance is growing in most of the protected areas. Boars were recorded mostly in wetlands, forest and shrublands. Managers also reported a wide range of negative impacts, which included soil disturbance, vegetation damage and animal predation. Several control method types are used and in most protected areas, more than one are applied, but hunting was the most used technique. However, the effectiveness of control methods was low, suggesting the need of an urgent plan to define coordinated management actions to minimize the negative impacts of this species and also to prevent its expansion into new areas.